Radiotherapy induces responses of lung cancer to CTLA-4 blockade. (December 2018) - Formenti, Silvia; Rudqvist, Nils-Petter; Golden, Encouse; Cooper, Benjamin; Wennerberg, Erik; Lhuillier, Claire; Vanpouille-Box, Claire; Friedman, Kent; Ferrari de Andrade, Lucas; Wucherpfennig, Kai; Heguy, Adriana; Imai, Naoko; et al.
Abstract Focal radiation therapy enhances systemic responses to anti-CTLA-4 antibodies in preclinical studies and in some patients with melanoma1–3, but its efficacy in inducing systemic responses (abscopal responses) against tumors unresponsive to CTLA-4 blockade remained uncertain. Radiation therapy promotes the activation of anti-tumor T cells, an effect dependent on type I interferon induction in the irradiated tumor4–6 . The latter is essential for achieving abscopal responses in murine cancers6 . The mechanisms underlying abscopal responses in patients treated with radiation therapy and CTLA-4 blockade remain unclear. Here we report that radiation therapy and CTLA-4 blockade induced systemic anti-tumor T cells in chemo-refractory metastatic non-small-cell lung cancer (NSCLC), where anti-CTLA-4 antibodies had failed to demonstrate significant efficacy alone or in combination with chemotherapy7, 8 . Objective responses were observed in 18% of enrolled patients, and 31% had disease control. Increased serum interferon-β after radiation and early dynamic changes of blood T cell clones were the strongest response predictors, confirming preclinical mechanistic data. Functional analysis in one responding patient showed the rapid in vivo expansion of CD8 T cells recognizing a neoantigen encoded in a gene upregulated by radiation, supporting the hypothesis that one explanation for the abscopal response is radiation-induced exposure of immunogenic mutations to the immune system. Radiotherapy-induced abscopal responses enhance the efficacy of anti-CTLA-4 in patients with non-small-cell lung cancer.